2020
DOI: 10.1002/admt.202000191
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Transient Biomemristor Based on Hybrid Structure HfO2/BSA:Au Double Layers

Abstract: applied and realized in new emerging memristors (i.e., resistive switching (RS)) devices, such as spider silk, silk fibroin, and egg albumen, and have been adopted as a functional layer to prepare the memristor cell. [1,2] Biomemristors have the advantages of low costs and being environmentally friendly, and they can be used to mimic the biosynapse function or nonvolatile memory to meet the need for sustainable development of electronic devices. Because of the unique advantages and potential applicability of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Among electrode materials, due to their excellent mechanical properties, metals and oxides are promising flexible memristor electrode materials. Some of these metal materials have high conductivity and flexibility, such as Ti [22], Mg [23], Ag [24], and W [25]. These materials are used in the preparation of flexible memristors.…”
Section: Flexible Electrode Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among electrode materials, due to their excellent mechanical properties, metals and oxides are promising flexible memristor electrode materials. Some of these metal materials have high conductivity and flexibility, such as Ti [22], Mg [23], Ag [24], and W [25]. These materials are used in the preparation of flexible memristors.…”
Section: Flexible Electrode Materialsmentioning
confidence: 99%
“…They have been used as the functional layer for the preparation of memristor units and have a wide range of applications in electronic skin, biomedicine, and brain chip applications [76]. Li et al [24] used bovine serum albumin: gold as the dielectric layer and added a layer of hafnium between the intermediate layer and the electrode to stabilize the relative performance of the device. Ag/HfO 2 /BSA:Au/Pt was prepared on a polydimethylsiloxane flexible substrate to check the functional performance of biological systems under bending conditions.…”
Section: Biodegradable Materials: Flexible Memristormentioning
confidence: 99%
See 1 more Smart Citation
“…[18,[29][30][31] In this regard, Park et al [18] reported artificial synapses in lignin-based bio-memristor devices, lignin is biodegradable and the abundant renewable material extracted from plants. Li et al [32] reported a bio-memristor based synaptic device with a hybrid structure of Ag/HfO 2 /BSA:Au/Pt. They used hybrid biomaterial of bovine serum doped with nano-gold (BSA:Au) and HfO 2 double layers as insulating switching layer materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, flexible electronic devices have unique mechanical properties, including foldability, extensibility, and flexibility, which have caused great changes in fields including collapsible display screens, electronic-skin devices, , wearable sensors, , and biomedicines . Additionally, new conceptual flexible neuromorphic devices have also attracted attention. Very recently, advanced electronic platforms have been synergistically integrated with neuromorphic devices to build artificial perceptual neuromorphic platforms with the function of touch, sight, hearing, etc. ,, Such perceptual cognitive systems would have great potential in fields including but not limited to replacement neuroprosthetics and intelligent humanoid robots. , Particularly, wearable electronic systems would be endowed with new functions when integrating flexible neuromorphic devices with signal processing functions. They would execute information processing and decoding in-situ and help improve perception accuracy and responsiveness.…”
Section: Introductionmentioning
confidence: 99%